The Study of Isomeric Ratios in Photonuclear Reactions Forming High Spin Isomers in the Giant Dipole Resonance Region - Thiep, Tran Duc; An, Truong Thi; Cuong, Phan Viet; Vinh, Nguyen The; Hue, Bui Minh; Belov, A. G.; Maslov, O. D. (Communications in Physics, 2015)
We studied the isomeric ratios in odd-odd nuclei \(^{196}\)Au,\(^{182}\)Ta and \(^{194}\)Ir with high spin isomeric states produced in \(^{197}\)Au\((γ, n)\) \(^{196m,g}\)Au, \(^{183}\)W\((γ, p)\) \(^{182m,g}\)Ta and \(^{185}\)Pt\((γ, p)\)\(^{194m,g}\)Ir reactions by using the activation technique and \(γ\)-ray spectroscopic method in the giant dipole resonance (GDR) region. The high-purity natural Au, W and Pt foils in disc shape were irradiated with bremsstrahlungs generated from an electron accelerator Microtron. The irradiated foils were measured by the high resolution \(γ\)-ray spectroscopic system which consists of a Ge(HP) detector and a multichannel analyzer. In order to improve the accuracy of the experimental results, necessary corrections were made in the \(γ\)-ray activity measurements and data analysis. The results were analyzed, discussed and compared with those of other authors as well as with theoretical model calculations. The study shows that the isomeric ratios in nuclei with high spin isomeric states are much lower than that in low spin isomeric state isomers.